Peran Guru Agama Islam Dalam Mengembangankan Kecerdasan Emosional dan Spritual Siswa di Mi Al Ma’arif 07 Tunjungtirto Singosari - Qutub Tarqy Al Mahdy; Rosichin Mansur; Devi Wahyu Ertanti (VICRATINA, 2019)
The tendency of an increase in child students who experience emotional disturbances as the times develop. The decline in emotional and spiritual intelligence should be a concern, especially in the world of education. Madrasas as a vehicle for formal education and the role of teachers as educators are considered very strategic to shape the emotional and spiritual intelligence of students. MI Al Ma'arif 07 Malang is an educational institution that has tried to develop emotional and spiritual intelligence from an early stage in learning activities.From the background of the above research, the focus of the research is how the emotional and spiritual intelligence of students at MI Al Ma'arif 07 Tunjungtirto Singosari, how the role of Islamic religious teachers in developing students' emotional and spiritual intelligence in MI Al Ma'arif 07 Tunjungtirto Singosari, know the supporting and inhibiting factors in developing emotional and spiritual intelligence in MI Al Ma’arif 07 Tunjungtiro Singosari.To achieve these objectives the research was conducted with a type of qualitative research. Data collection is done by conducting observations, interviews, and documentation. Data analysis is done by collecting data, reducing data, presenting data and drawing conclusions. Checking the validity of the data is done by using two kinds of triangulation, namely source triangulation, technique triangulation, and time triangulation, and using peer techniques.The results showed the first that the emotional and spiritual intelligence of students is done well, by way of implementing an emotional and spiritual intelligence development program there are several ways that can be implemented several ways including through religious activities, through the task, through the path of nurturing, through the path of knowledge , through the path of personal change, through the path of brotherhood the educator must encourage students to share with each other.The role of the Islamic teacher in developing emotional and spiritual intelligence of students is by habituating religious activities, controlled activities in teaching and learning activities, discipline of all school members, awareness of all school members to obey school rules, teacher motivation to students, punishment and appreciation